Oxford Nanopore Technologies (ONT) Full-length Transcriptomics Shows Electroacupuncture Ameliorates Lipid Metabolic Disorder through Suppressing Hepatic Pdia3/Perk/Qrich1 Expression in Rats - Zhang, Pu; Li, Yue; Zhang, Ning; Wang, Xiao-gang; Qu, Yan-wei; Pei, Hui; Liu, Xiao-chun; Liu, Qi; Lv, Pei-ran; Zhao, Xian (Combinatorial Chemistry & High Throughput Screening, 2025)
BackgroundThe incidence of dyslipidemia increases after menopause. Electroacupuncture (EA) has been recommended for menopause-related disease. However, the positive effect on lipid metabolism disorders is still unclear.ObjectivesTo investigate the underlying mechanism of EA treatment on lipid metabolism disorders through ONT full-length transcriptome sequencingMethodsAdult female SD rats were randomly divided into Ctrl, sham operation+high-fat feed(Sham+HFD), Ovariectomized+high-fat feed (OVX+HFD), Ovariectomized+high-fat feed + Atorvastatin (OVX+HFD+ATO) and OVX+HFD+EA groups. Periovarian adipose tissue around the bilateral ovaries of rats in the Sham+HFD group was resected. Rats in the OVX+HFD, OVX+HFD+ATO and OVX+HFD+EA groups were subjected to bilateral oophorectomy to prepare the ovariectomized rat model. Treatment was applied to rats in the OVX+HFD+EA group. ST36, PC6, SP6, BL18 and ST40 were the selected acupoints. Daily food intake and body weights of rats were recorded. The samples were collected 30 days after treatment. The serum levels of total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein (HDL-C) were detected to assess the improvement of lipid metabolism disorders. HE and oil red O staining were used to stain the liver tissues. Total RNA was extracted from liver tissues, and its transcriptional changes were determined by high-throughput sequencing. Additionally, RT-qPCR and immunofluorescence staining were used to verify the crucial signal pathway screened by the ONT full-length transcriptome sequencing.ResultsEA treatment resulted in a lowered weight of perirenal fat and liver and a significant improvement in the color of the liver. In addition, EA could improve the lipid profile and hepatic steatosis in OVX+HFD rats. According to full-length transcriptome sequencing, 2292 genes showed differential expression in the OVX+HFD group; of these, 1121 were upregulated and 1171 down-regulated. 609 DEGs were found in the OVX+HFD+EA group compared to the OVX+HFD group; 235 up-regulated and 374 down-regulated. We also found that 77 genes are significantly upregulated after EA intervention through Venn map analysis (including Agtr1a, Pdia3, etc.), which may be the targeted genes for EA treatment of lipid metabolism disorders. Finally, we verified the expression of Pdia3, Perk and Qrich1 levels in liver tissues. HFD feeding could increase the expression of Pdia3 and its downstream signal pathways molecular Perk and Qrich1. But these effects were reversed by EA treatment, the results demonstrated that the expression of pdia3, Perk, as well as Qrich1 of OVX+HFD rats had a decreasing trend after EA treatment.ConclusionsEA could ameliorate lipid metabolic disorder in OVX+HFD rats. The Pdia3/Perk/Qrich1 signal pathway may play crucial roles in the improvement of lipid metabolism disorder of OVX+HFD rats after EA treatment.
Keywords: Pdia3